ANALISIS PENGARUH KEDISIPLINAN, GAYA KEPEMIMPINAN, DAN MOTIVASI TERHADAP KINERJA KARYAWAN (Studi Pada Perusahaan Otobus Jaya Indah Semarang) - Hartanto, Arie Pramudhita; Rahardjo, Edy (Diponegoro Journal of Management, 2016)
This research is motivated the need for a good performance for the Company's employees Otobus Jaya Indah as buses. The existence of this Indah Jaya Otobus Company as a tourist bus service providers located in Semarang need to be considered, as should be well prepared in every way to support the existence of PO. The Indah Jaya. This study aimed to examine the influence of discipline, leadership styles, and motivation on the performance of the Company's employees Otobus Jaya Indah Semarang.This study uses census techniques with a sample of the population amounted to 50 Company employees Otobus Jaya Indah Semarang. The analytical method used is multiple linear regression. Results of the study found that the regression equation as follows: Y = 0447 X1 + 0.456 X2 + 0.639 X3.Based on statistical data analysis, indicators in this study are valid and reliable. In the classic assumption test, regression model multicoloniarityfree, does not occur heteroskedastisitas, and normal distribution. The biggest variable is the variable of motivation at 0.639, whereas the smallest variable variable discipline at 0.447. Results of the study found that all independent variables positive and significant effect on the dependent variable.